Recovery of high specific area silica and sodium fluoride from sodium hexafluorosilicate - Xu, Hui; Li, Gui; Cheng, Jun-feng; Liu, Wei-ping (Journal of Central South University, 2014)
Sodium fluoride and high specific area silica were synthesized by using sodium hexafluorosilicate (Na 2 SiF 6 ) and sodium carbonate decahydrate (Na 2 CO 3 ·10H 2 O). The influencing factors of react temperature, contact time, sodium dodecyl sulfate (SDS) and molar ratio of Na 2 SiF 6 to Na 2 CO 3 ·10H 2 O were investigated. The optimum process involves the reaction of 0.075 mol Na 2 SiF 6 and 150 mL, 0.225 mol Na 2 CO 3 ·10H 2 O (molar ratio of 1:3) at 85 °C for 90 min, and 2.0×10 −3 mol sodium dodecyl sulfate (SDS) as additive. The results show that the purities of SiO 2 and NaF at extraction yields of 96.5% and 98.0% are 91.0% and 98.6%, respectively. The obtained SiO 2 were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), Fourier transform infrared ray (FTIR), differential scanning calorimetry and thermogravimetric analysis (DSC-TGA), N 2 absorption/desorption (BET) and laser particle size analyzer. The result demonstrates that SiO 2 particles have a high BET surface area of 103 m 2 /g, and a mean grain size of 985 nm.